2012
DOI: 10.1016/j.pbb.2012.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Double-dissociation of D1 and opioid receptor antagonism effects on the acquisition of sucrose-conditioned flavor preferences in BALB/c and SWR mice

Abstract: Sugar appetite is influenced by unlearned attractions to sweet taste and learned responses to sugars’ taste and post-ingestive actions. In rats, sugar-conditioned flavor preferences (CFP) are attenuated by dopamine D1 (SCH23390: SCH), but not opioid (naltrexone: NTX), receptor antagonism. Sucrose-CFP occurs in BALB/c and SWR inbred mice that differ in their suppressive effects of SCH and NTX on sucrose intake. The present study examined whether SCH and NTX altered expression of a previously learned sucrose-CFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 37 publications
3
24
2
Order By: Relevance
“…During testing, mice had the same dietary regime, but they had the option between regular tap water and either sucrose (1 %) or saccharine (0.05 %) solutions, presented in graduated 100-mL glass bottles with a drinking well that extended 4 cm into the cage. Concentrations of sucrose and saccharin were chosen following the ones used by other authors [29][30][31][32]. Bottles were placed symmetrically on the food container, and they were switched every day to avoid position preference.…”
Section: Two-bottle Choice Testmentioning
confidence: 99%
“…During testing, mice had the same dietary regime, but they had the option between regular tap water and either sucrose (1 %) or saccharine (0.05 %) solutions, presented in graduated 100-mL glass bottles with a drinking well that extended 4 cm into the cage. Concentrations of sucrose and saccharin were chosen following the ones used by other authors [29][30][31][32]. Bottles were placed symmetrically on the food container, and they were switched every day to avoid position preference.…”
Section: Two-bottle Choice Testmentioning
confidence: 99%
“…Whereas sucrose-CFP expression in both BALB/c and SWR mice was significantly reduced by SCH and NTX, sucrose-CFP acquisition was significantly reduced by NTX, but not SCH in BALB/c mice, and by SCH, but not NTX in SWR mice (Dym et al, 2012). A subsequent study (Kraft et al, 2013) demonstrated that these strains displayed fat (Intralipid)-CFP, and that its acquisition and expression were significantly reduced by SCH and NTX in BALB/c mice, but only by SCH in SWR mice.…”
Section: Introductionmentioning
confidence: 81%
“…Two of these inbred strains, SWR and BALB/c mice, displayed the most robust and durable sucrose-CFP (Pinhas et al, 2012) and thus Pharmacology, Biochemistry and Behavior 131 (2015) 13-18 were evaluated for DA D1 and opioid antagonist mediation of the expression and acquisition of sucrose-CFP (Dym et al, 2012). Whereas sucrose-CFP expression in both BALB/c and SWR mice was significantly reduced by SCH and NTX, sucrose-CFP acquisition was significantly reduced by NTX, but not SCH in BALB/c mice, and by SCH, but not NTX in SWR mice (Dym et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, opioid receptor antagonism with naltrexone failed to affect the acquisition or expression of CFPs in rats produced by IG sucrose or orally-consumed fructose (Azzara et al, 2000;Baker et al, 2004). Studies of SWR and BALB/c mice revealed that the expression of a CFP produced by oral sucrose was attenuated by both DA D1-like and opioid antagonists (Dym et al, 2012). In contrast, acquisition of sucrose-CFP was reduced by opioid, but not DA D1 antagonism in BALB/c mice, and by DA D1, but not opioid antagonism in SWR mice, indicating a double dissociation in the pharmacological effects on sucrose-CFP in the two strains (Dym et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…Studies of SWR and BALB/c mice revealed that the expression of a CFP produced by oral sucrose was attenuated by both DA D1-like and opioid antagonists (Dym et al, 2012). In contrast, acquisition of sucrose-CFP was reduced by opioid, but not DA D1 antagonism in BALB/c mice, and by DA D1, but not opioid antagonism in SWR mice, indicating a double dissociation in the pharmacological effects on sucrose-CFP in the two strains (Dym et al, 2012). A different pattern of drug effects were observed in mice trained with oral fructose (Kraft et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%